2013
DOI: 10.1177/0091026013495773
|View full text |Cite
|
Sign up to set email alerts
|

The New Public Service? Applying the Public Service Motivation Model to Nonprofit Employees

Abstract: Research in the for-profit and public sectors has long sought to understand the factors affecting employee motivation but little is known concerning motivation of the nonprofit workforce. It has been suggested that nonprofit employees are an integral part of the new public service and are in many ways motivated to serve similar to public employees. To test this notion, this research presents an adapted version of Perry’s Public Service Motivation (PSM) Scale to examine motivation of nonprofit sector employees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 22 publications
4
49
0
1
Order By: Relevance
“…Only recently has it been noted that third-sector employees also share similar concern with services that enrich communities and civil society (e.g., Mann 2006; Park and Word 2012). As a difference to the public sector, however, it seems to be that thirdsector employees are not that interested in policy making (Word and Carpenter 2013) or servicing the public and public good, but instead their service motivation is more related to the local level (Lee and Wilkins 2011).…”
Section: Toward Work Engagement's Conceptual Model In the Third Sectormentioning
confidence: 99%
“…Only recently has it been noted that third-sector employees also share similar concern with services that enrich communities and civil society (e.g., Mann 2006; Park and Word 2012). As a difference to the public sector, however, it seems to be that thirdsector employees are not that interested in policy making (Word and Carpenter 2013) or servicing the public and public good, but instead their service motivation is more related to the local level (Lee and Wilkins 2011).…”
Section: Toward Work Engagement's Conceptual Model In the Third Sectormentioning
confidence: 99%
“…While little research has explicitly examined the role of spirituality in these fields, the idea of work as a calling underpins many of the descriptions of work in the public and nonprofit sectors. Underlying the examination of motivation to work in these sectors is the idea of altruism or service to others (Houston and Cartwright 2007, Word and Carpenter 2010. The idea of work as a calling has a particular relevance in public and nonprofit work as it often engages employees in jobs that impact the lives of others in ways that are meaningful for the recipients of services and society.…”
Section: Work As a Callingmentioning
confidence: 99%
“…Compassion is defined as having a general love for people (Word and Carpenter 2013) A PSM study in Denmark found nurses had higher levels of compassion and increased job satisfaction (Andersen and Kjeldsen 2013). Liu et al (2014) also found evidence that high levels of compassion increased job satisfaction though amongst Chinese social workers.…”
Section: Compassionmentioning
confidence: 99%
“…However, other scholars see the key role of social justice is to help those in society that are seen as underserved (Word and Carpenter 2013). Campaigns for change at community levels are increasingly prevalent (Cairns et al 2010).…”
Section: Social Justicementioning
confidence: 99%